The Effect of Fibers' Length Distribution and Concentration on Rheological and Mechanical Properties of Glass Fiber–Reinforced Polypropylene Composite. Issue 5 (June 2022) - Asoodeh, Fatemeh; Aghvami-Panah, Mohammad; Salimian, Saeed; Naeimirad, Mohammadreza; khoshnevis, Hamed; Zadhoush, Ali
This article aims to investigate the effect of dispersion and uniformity of fiber length distribution on the rheological and mechanical behavior of polypropylene reinforced with short glass fiber. The composites were prepared through melt compounding with three various glass fiber concentrations using a twin-screw extruder. Multiple extrusion processing was used to alter and manipulate the fibers' length inside the composites. The fiber length distribution was analyzed via the photomicrograph technique. Rheological measurements indicated that the molten samples were visco-plastic fluids and the Herschel–Bulkley model is the best model for fitting on the rheological behavior diagram. Variables of the fitted model are noticeably altered by the fiber length distribution. Moreover, rheological assessments revealed that the non-Newtonian behavior of the molten composites significantly diminished after the second extrusion processing, while it did not have much effect on the fiber length reduction. In the second phase, tensile and flexural properties were determined to detect the mechanical properties. The results indicated that the tensile strength of the composite has a direct relation with the fiber length distribution factor while the flexural strength is independent of fiber length. Furthermore, the highest tensile and flexural strength attained from the composite containing the highest fiber volume fraction.